Synthesis of Dibromo[3.3]paracyclophanes - Shibahara, Masahiko; Watanabe, Motonori; Miyazaki, Takaaki; Goto, Kenta; Matsumoto, Taisuke; Shinmyozu, Teruo (Synthesis, 2016)
All possible pseudogeminal-, pseudoortho-, pseudometa-, and pseudopara-dibromo[3.3]paracyclophanes were synthesized by the (p-tolylsulfonyl)methyl isocyanide (TosMIC) coupling method, and characterized by the aromatic proton signals of the 1H NMR spectra and finally by the X-ray crystal structure analyses of the pseudogeminal, pseudoortho, and pseudopara isomers.
Keywords: cyclophanes; NMR; X-ray crystal structure; coupling reaction; Wolff–Kishner reduction